Penerapan Metode Haar Wavelet Transform Dalam Teknik Pemampatan Citra Berwarna - Arief Satria; Abdul Sani Sembiring; Fadlina Fadlina (JURIKOM (Jurnal Riset Komputer), 2018)
Image is a process of processing and analysis that involves a lot of visual perceptions that can make information-rich, but often the image that we have has a decrease in quality intensity and difficult to represent so that the information becomes less attractive images from simple images that exist. Image compression technique is done to reduce the storage space needs of the image and bandwidth requirements in the image processing process the larger the image size, the longer the processing time is needed. Wavelets are defined as small waves. Wavelet transform will convert a signal into a wavelet array. In haar wavelet transformation consists of two processes that must be carried out, namely decomposition transformation and reconstruction transformation. Decomposition transformation is useful for dividing parts of a picture. While the reconstruction transformation is the opposite, that is reshaping the parts of the image from the forward decomposition process to an original image. As for image compression is done to reduce the need for image storage space and bandwidth requirements in the image processing process the larger the image size, the longer the processing time required.